Bile acid biosynthesis in Smith-Lemli-Opitz syndrome bypassing cholesterol: Potential importance of pathway intermediates. Issue 206 (February 2021) - Abdel-Khalik, Jonas; Hearn, Thomas; Dickson, Alison L.; Crick, Peter J.; Yutuc, Eylan; Austin-Muttitt, Karl; Bigger, Brian W.; Morris, Andrew A.; Shackleton, Cedric H.; Clayton, Peter T.; Iida, Takashi; Sircar, Ria; et al.
Highlights: New pathway of bile acid biosynthesis avoiding cholesterol. Mechanism for biosynthesis of 3β, 7β-dihydroxy-5-ene bile acids. Biosynthesis of 3β-hydroxy-7-oxo-5-ene bile acids. Pathway intermediates bind to and activate Smo. A new link between SLOS and deranged Hh signalling. Abstract: Bile acids are the end products of cholesterol metabolism secreted into bile. They are essential for the absorption of lipids and lipid soluble compounds from the intestine. Here we have identified a series of unusual Δ 5 -unsaturated bile acids in plasma and urine of patients with Smith-Lemli-Opitz syndrome (SLOS), a defect in cholesterol biosynthesis resulting in elevated levels of 7-dehydrocholesterol (7-DHC), an immediate precursor of cholesterol. Using liquid chromatography – mass spectrometry (LC–MS) we have uncovered a pathway of bile acid biosynthesis in SLOS avoiding cholesterol starting with 7-DHC and proceeding through 7-oxo and 7β-hydroxy intermediates. This pathway also occurs to a minor extent in healthy humans, but elevated levels of pathway intermediates could be responsible for some of the features SLOS. The pathway is also active in SLOS affected pregnancies as revealed by analysis of amniotic fluid. Importantly, intermediates in the pathway, 25-hydroxy-7-oxocholesterol, (25R)26-hydroxy-7-oxocholesterol, 3β-hydroxy-7-oxocholest-5-en-(25R)26-oic acid and the analogous 7β-hydroxysterols are modulators of the activity of Smoothened (Smo), an oncoprotein that mediates Hedgehog (Hh) signalling across membranes during embryogenesis and in the regeneration of postembryonic tissue. Computational docking of the 7-oxo and 7β-hydroxy compounds to the extracellular cysteine rich domain of Smo reveals that they bind in the same groove as both 20S-hydroxycholesterol and cholesterol, known activators of the Hh pathway.